Constructivist model to encounter language misconseptions, prior knowledge overgeneralizations and visualization errors in electrochemistry - Akram, Muzammila (2016)
The problem of misconceptions has become more critical when students have to acquire science concepts in a second language. Moreover, students? misconceptions might vary by region, culture, gender or age and to students with the misconceptions, it is essential to identify the reasons behind it. The present study identified the misconceptions in electrochemistry, and reasons for these misconceptions among second language science students of a secondary class in Pakistan. Many researchers have indicated that electrochemistry is considered a difficult topic for students to learn. The research developed a constructivist model to encounter language misconceptions, prior knowledge overgeneralizations and visualization errors after identifying electrochemistry misconceptions. It was conducted in two phases. During phase-I, grounded theory was used to identify electrochemistry misconceptions and its reasons, and a model in light of constructivist theories was developed. Data were collected via Test designed to identify Misconceptions in Electrochemistry, diagnostic test interview, think aloud protocol, concept mapping, and eminent chemistry teachers. In phase-II, the process of teaching using the new model was observed after training was given to two volunteer teachers. Students who had studied based on the new model were purposively selected for an interview. The findings of phase-I data were used to develop a Constructivist Model to Encounter the Misconceptions in electrochemistry. The findings of phase-II showed that model was effective to encounter language misconceptions, prior knowledge overgeneralizations and visualization errors in electrochemistry. The present study concluded that the diagnosed misconceptions helped to produce a disequilibrium state among second language science students leading to assimilation and accommodation. In this study, second language science students were found to use complex content related vocabulary and technical terms in the presence of a more knowledgeable person (teacher and peer in the zone of proximal development)